PERANAN PENYULUH AGAMA DALAM MEMBERIKAN BIMBINGAN TERHADAP CALON MEMPELAI DI KANTOR URUSAN AGAMA (KUA) KECAMATAN KLOJEN KOTA MALANG - Nabilah Lukman Manu; Ahmad Subekti; Fathurrahman Alfa (Jurnal Hikmatina, 2020)
The role of religious counselors is very important, because it is expected to be able to provide wise guidance to the two brides who want to get married. So there is no compulsion in marriage or other obstacles to get married. Therefore, a Islamic Counselor in the Office of Religious Affairs in the Klojen District of Malang City continue to try to provide counseling as a way of preaching to convey Islamic knowledge to become a provision marriage for the bride and groom who will get married. Through this study, a researcher interested in conducting research that will focus on her studies about the role of a religious counselor in providing guidance to the bride and groom, so that the realization of a sakinah, mawadah, warahmah family. This research uses qualitative research which is located in the Office of Religious Affairs in Klojen District in Malang City. The research approach used is a psychological approach. Sources of data in this study are primary data sources and secondary data sources. Data collection techniques used were observation, interview, and documentation techniques. The implications of this study are for every bride and groom before entering into a marriage contract, they are should know their respective backgrounds. And the most important thing for the bride and groom is to increase the knowledge of religion in order to stabilize themselves for their partners. Because only with religion can happiness be achieved in family life, then whenever there are problems they are able to solve it independently. Keywords: The Role of Religious Counselor, Counseling, Bride and Groom.